TWO NEW SPECIES OF THE GENUS PARAMAZOCRAES TRIPATHI, 1959, FROM A FRESHWATER FISH, SCIAENA COITOR (HAM.) - SINGH, H. S.; AGARWAL, SHILPI; KUMAR, KAPIL; ., VIBHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
The present communication deals with two new species of monogeneans belonging to genus Pramazocraes Tripathi, 1959. The P. guptain.sp. is characterised in having different shape of oral sucker, presence of pharyngial glands, arrangement of genital hooks and number of testis. However, Pyogendrain.sp. is characterised in having difference in the shape of oral suckers, difference in organisation of clamp skeleton and disposition of genital hooks.